2021
DOI: 10.1609/icwsm.v5i1.14101
|View full text |Cite
|
Sign up to set email alerts
|

Two Paths of Glory — Structural Positions and Trajectories of Websites within Their Topical Territory

Abstract: We analyze the structure and processes of reputation building in a sample of Internet communities. Our approach uses a corpus of around 9,000 'active' French websites and blogs which have been manually labeled as belonging to a specific topical territory, such as "cooking", "crafts", or "politics". We propose a typology and map of the various structural positions that these websites may hold within their territory. This typology is essentially based on their authority status in terms of in- and out-going li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…The other slots are under-represented, a finding consistent with the typical structure observed in cases corresponding specifically to online deliberative spaces when adopting a purely semantic understanding of the heart (Cardon et al, 2011). The central slots of the matrix (B2-C2-B3-C3) are almost non-existent (especially C3 which corresponds to a heart-centric pattern where activity and authority relate exclusively to the heart with no regard to the shadow).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The other slots are under-represented, a finding consistent with the typical structure observed in cases corresponding specifically to online deliberative spaces when adopting a purely semantic understanding of the heart (Cardon et al, 2011). The central slots of the matrix (B2-C2-B3-C3) are almost non-existent (especially C3 which corresponds to a heart-centric pattern where activity and authority relate exclusively to the heart with no regard to the shadow).…”
Section: Resultssupporting
confidence: 66%
“…Structural model. We use and extend a structural model that had been introduced by Cardon et al (2011) in the analysis of blogspace. This model is based on a so-called "A1-D4" matrix and allows for the description of position classes defined with respect to the relative attention that nodes give and receive from inside and outside of a target group of actors (a specific group of interest).…”
Section: Configurations and Positionsmentioning
confidence: 99%
“…They developed K-Spectral Centroid clustering algorithm and found six temporal shapes of attention of online content on the twitter dataset. (Cardon, Fouetillou, and Roth 2011) studied topic specific website and blogs over 10 months and suggested that there are two ways to build authority -either by developing reputation progressively or by exploiting prior acquired fame. They illustrated these two phenomenon in the blogosphere and showed trajectories leading towards gaining online reputation.…”
Section: Temporal Analysis Of Usersmentioning
confidence: 99%